The Impact of Autonomous Listening Practices on Students' Proficiency in Interpretive Listening Courses - Desak Ketut Meirawati; Radita Yuda Pradana Wayan; Yoga Yasa I Made (Universitas Pendidikan Ganesha, 2025)
The implementation of the Autonomous Listening Activity is designed to improve students' attitudes, participation, and active listening strategies, enabling more effective learning patterns during lectures. This study aims to analyze Autonomous Listening Activity on students' interpretive listening abilities in the Interpretive Listening course. The study used a quasi-experimental design with a pretest–posttest control group, involving 38 students: 19 in the experimental class and 19 in the control class. The research instruments included a listening ability test, a response questionnaire, and an observation sheet. Data analysis was conducted using normality and homogeneity tests, t-tests, F-tests, and regression analysis to determine the magnitude of the influence of Autonomous Listening Activity. The results showed that students responded positively to the implementation of this independent learning. Based on the regression results, Autonomous Listening Activity had a 15.7% effect on improving students' listening abilities. In detail, Autonomous in Attitude contributed 0.2%, Autonomous in Participation 2.1%, and Autonomous in Listening 35%. These findings emphasize the importance of structured, independent listening activities for improving students' auditory interpretation skills. The implications of this research contribute to the development of more effective English language learning methods, particularly in teaching interpretive listening skills.